PENGARUH PENERAPAN TIPE JIGSAW TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PESERTA DIDIK DI SEKOLAH DASAR - Deviyanti, Putri; Sabri, Tahmid; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the influence of application the jigsaw type to the learning outcomes of Civic Education students in Primary School. The method used is the experimental method. This research using Pre-Experimental Design with form One-Group Pretest-Posttest Design. The sample of this research are all students in grade IV SD 15 Pontianak Selatan with a total of 21 students. The data collection technique is a measurement technique. The data collection tool used is a test. Based on the data analysis, the result of average pre-test is 50,05 and post-test is 56,71. After t-test is obtained tcount of 1,84,while ttable with db = 2 –1 = 20 and significant level (α) = 5% is 1,725, it turns out tcount > ttable or 1,84 > 1,725, then Ha accepted. So, it can be concluded that there is an influence of application the jigsaw type to the learning outcomes of Civic Education students in Primary School. Based on the results of the calculation of the effect size obtained 0,36 which is classified in the medium category, namely in the range of effect size of .50 is medium. Thus it can be said that application the jigsaw type gives a medium influence on the learning outcomes of Civic Education students in Primary School. Keywords: Influence, Jigsaw Type, Learning Outcomes Of Students, Civic Education